Society Partnership Program Otak-Otak of Milkfish in Gresik Regency East Java Province - admin; Yayah Atmajawati; Wininatin Khamimah (Kontribusia : Research Dissemination for Community Development, 2018)
The amount of small and medium enterprises (SME) in Gresik Regency continues to increase; this makes the Regional Government of Gresik Regency through the Department of Cooperatives, SME, Industry and Trade have difficulties in conducting coaching as a whole. Society Partnership Program Team intends to help the Department of Cooperatives, SME, Industry and Trade Gresik Regency in conducting coaching through training to SME otak-otak of milkfish. The purpose of Society Partnership Program activity to help SME otak-otak of milkfish in solving the problems faced, such as: not knowing how to make the right financial report and do not have the media marketing online (e-commerce). Coaching activities through training to SME otak-otak of milkfish cover several activities, namely: 1) presentation of financial and e-commerce report, 2) practice of making the correct financial report, 3) practice of operating e-commerce. From the results of the implementation of Society Partnership Program activities, such as : 1) Improve the ability and knowledge in making financial statements used to find out income received, production costs incurred, and as one of the requirements in the filing of credit, 2) Improve skills in online marketing through e-commerce used to market products that have unlimited access and efficient.